Internal Control System and Audit Opinion: Case from South Sulawesi in Indonesia - Achdian Anggreny Bangsawan; Ahmad Abbas (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2022)
This research aims at testing the effect of internal control system on the audit opinion. The type of this research is quantitative. The sample of this research was local governments in South Sulawesi of Indonesia. The data were analyzed using ordinal logistic regression. The result of this research found that internal control system identified through weaknesses in the accounting and reporting system, the control system of the implementation of revenue and expenditure budget, and the internal control structure, have negative effects on the audit opinion of financial statements. The higher the weaknesses found in the internal control system, the more difficult the local governments to obtain unqualified opinion